Lipoxygenase and urease inhibition of the aerial parts of the Polygonatum verticillatum. (August 2015) - Khan, Haroon; Saeed, Muhammad; Muhammad, Naveed; Gaffar, Rukhsana; Gul, Farah; Raziq, Naila
Over expression of lipoxygenase (LOX) and urease has already contributed to the pathology of different human disease. Targeting the inhibition of these enzymes has proved great clinical utility. The aim of the present study was to scrutinised the inhibitory profile of the aerial parts of the Polygonatum verticillatum enzyme against LOX, urease, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) using standard experimental protocols. When checked against lipoxygenase, the extracts revealed significant attenuation. Of the tested extracts, the ethyl acetate fraction was the most potent (half-maximal inhibitory concentration (IC50 ): 97 µg/mL) followed by aqueous fraction IC50 : 109 µg/mL). Regarding urease inhibition, n -butanol was the most potent fraction (IC50 : 97 µg/mL). However, the extracts did not show significant inhibition on AChE and BChE. In the preliminary phytochemical tests, the aerial parts of the plant showed the presence of saponins, alkaloids, flavonoids, phenols, tannins and terpenoids. The current findings could be attributed to these groups of compounds.